2006
DOI: 10.1038/emm.2006.72
|View full text |Cite
|
Sign up to set email alerts
|

4-1BB (CD137) signals depend upon CD28 signals in alloimmune responses

Abstract: Our previous study has demonstrated that there is a significant delay of Balb/c cardiac allograft rejection in the C57BL/6 4-1BB-deficient knockout recipient. In this study, we examined the effect of combined blockade of the 4-1BB and CD28 costimulatory pathways on cardiac allograft rejection in the C57BL/6 → Balb/c model. A long-term cardiac allograft survival was induced in CD28/4-1BB-deficient mice (> 100 days survival in 3 of 4 mice), which was comparable with CD28-deficient mice (> 100 days survival in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…14 CD137 has been shown to be essential for B-cell function, including activation, affinity maturation, proliferation, and class switch recombination (CSR) through its interaction with CD137L in germinal centers. [14][15][16] We thus hypothesized that these functions may be impaired in patient B cells. Indeed, CD137 expression was abrogated in B cells from all patients (Figure 1F), and B-cell activation was impaired (Figure 2G).…”
Section: Functional T-cell Defects In Cd137-deficient Patientsmentioning
confidence: 99%
“…14 CD137 has been shown to be essential for B-cell function, including activation, affinity maturation, proliferation, and class switch recombination (CSR) through its interaction with CD137L in germinal centers. [14][15][16] We thus hypothesized that these functions may be impaired in patient B cells. Indeed, CD137 expression was abrogated in B cells from all patients (Figure 1F), and B-cell activation was impaired (Figure 2G).…”
Section: Functional T-cell Defects In Cd137-deficient Patientsmentioning
confidence: 99%
“…Hence, we used magnetic beads (Dynabeads) coated with mAbs for CD3, CD28 and CD137 as novel artificial APCs to provide activation ‘signal 1’ via the TCR and to combine it with a strong costimulatory ‘signal 2’. Because it is not yet clear from the literature, whether CD137 acts as an independent costimulatory signal [31, 32] or is depending on CD28 signalling [33, 34], we applied CD3/CD28/CD137 beads and compared them with conventional CD3/CD28 beads. Some studies have already indicated that binding of agonistic antibodies to CD137 mediates an antigen‐independent growth signal for T lymphocytes with memory phenotype [35].…”
Section: Discussionmentioning
confidence: 99%
“…CD137 is a member of the TNF receptor family and its expression is inducible in T cells (14,15). Induction of CD137 can be triggered by TCR signaling and CD28 signaling further increases TCR-mediated upregulation of CD137 expression, suggesting that CD137 signaling is dependent upon CD28 signaling (16). Nonetheless, CD137 is thought to have distinct roles in T-cell-mediated immune responses.…”
Section: T-cell Costimulationmentioning
confidence: 99%